Effect of Conductive Coating on Silver/Silver Chloride Electrodes for Cathodic Protection Application - Herlambang, Karyanto; Pradipta Dwi Briyantama (HM Publisher, 2024)
Measurement of pipe to soil potential in a cathodic protection system is something that must be done which aims to monitor the performance of the installed cathodic protection system. The main measuring tool in measuring pipe to soil potential is the reference electrode. The stability of the reference electrode is important as a validation of the measurement results. So far, the stability of the reference electrode is very difficult to maintain due to frequent changes caused by the environment, especially for permanent reference electrodes that are buried in the underground or installed in seawater. Permanent reference electrode sensors commonly used in seawater is the Ag/AgCl reference electrode, but in fact the Ag/AgCl reference electrode is generally unstable and must be stabilized with a KCl solution and other problems have not been produced in Indonesia. This research will be carried out by adding a conductive layer to the Ag/AgCl electrode so that its stability can be increased. The sensor manufacturing process starts from pretreatment, electrolysis and product characterization. The results of the best coating thickness and weight gain experiments showed by the highest voltage variations and time variations (4000mV and 60 minutes). The presence of conductive solid material increases corrosion resistance from 0.00391 mm/year to 0.19549 mm/year and increases the stability of the Ag/AgCl layer ± 5 mV.